Adverse childhood experiences, mental health, substance use, and HIV-related outcomes among persons with HIV. Issue 10 (3rd October 2019) - Young-Wolff, Kelly C.; Sarovar, Varada; Sterling, Stacy A.; Leibowitz, Amy; McCaw, Brigid; Hare, Charles B.; Silverberg, Michael J.; Satre, Derek D.
ABSTRACT: While persons with HIV (PWH) have benefited from significant advances in treatment and resulting longevity, mental health problems remain elevated in this population. Adverse childhood experiences (ACEs) are common among PWH and may negatively affect mental health and HIV-related outcomes. We examined the association between ACEs, depression and anxiety symptoms, substance use, antiretroviral therapy (ART) adherence, and HIV-clinical indicators in a sample of 584 PWH at risk for unhealthy alcohol use enrolled in a primary care-based alcohol intervention study. The sample was 96.9% male, 63.0% non-Hispanic white, with an average age of 49.0 years. ACEs were highly prevalent: 82.5% reported ≥1 ACE, including 34.2% reporting 1–2 ACEs, 25.0% reporting 3–4 ACEs, and 23.3% reporting ≥5 ACEs. Adjusting for demographics, having 1–2, 3–4 or ≥5 ACEs was significantly associated with anxiety (ORs (95%CI): 3.41 (1.13–10.33), 4.36 (1.42–3.36), and 3.96 (1.28–12.19), respectively) and poorer mental health quality of life (Betas (SE): –3.21 (1.40), –6.23 (1.51), and –7.09 (1.54), respectively), but not with other outcomes. Trauma-informed interventions to reduce anxiety and improve mental health quality of life in PWH may reduce the negative health sequelae of ACEs.